Analisis Risiko Dalam Manajemen Perubahan Pendidikan Islam Transformatif: Strategi Mitigasi - Maulida, Rozamala; Maunah, Binti; Safi’i, Asrop; Zulmi Mahfudzi, Virdaus (J-MPI (Jurnal Manajemen Pendidikan Islam), 2025)
This research aims to analyze risks in the management of transformative Islamic education change and identify effective mitigation strategies. In the modern context, Islamic education experiences significant challenges in facing dynamic social, technological and cultural changes. Transformative change management is very necessary to ensure that Islamic education remains relevant and adaptive to current developments, but this process is not free from various risks. This research uses the library research method, utilizing various relevant literature sources, such as books, journals and academic articles, to identify and analyze risks that arise in the management of transformative Islamic education change. The research results show that the risks in change management in transformative Islamic education include resistance to change, limited resources, gaps in educational quality, potential value conflicts, unclear vision and goals, regulatory and policy obstacles, risk of less professional change management, technological challenges, dependency on external parties, lack of monitoring and evaluation. Through the implementation of appropriate mitigation strategies such as increasing human resource capacity, outreach and involvement of stakeholders, developing contextual and flexible curricula, strengthening policy frameworks and government support, these risks can be minimized. This research contributes to providing practical recommendations for Islamic educational institutions to manage change more effectively and sustainably.